Near-infrared absorbing Ru(ii) complexes act as immunoprotective photodynamic therapy (PDT) agents against aggressive melanoma. Issue 43 (9th October 2020) - Lifshits, Liubov M.; Roque III, John A.; Konda, Prathyusha; Monro, Susan; Cole, Houston D.; von Dohlen, David; Kim, Susy; Deep, Gagan; Thummel, Randolph P.; Cameron, Colin G.; Gujar, Shashi; McFarland, Sherri A.
Abstract : Ru(ii ) photosensitizers (PSs) destroy aggressive melanoma cells, triggering an immune response that leads to protection against tumor challenge and mouse survival. Abstract : Mounting evidence over the past 20 years suggests that photodynamic therapy (PDT), an anticancer modality known mostly as a local treatment, has the capacity to invoke a systemic antitumor immune response, leading to protection against tumor recurrence. For aggressive cancers such as melanoma, where chemotherapy and radiotherapy are ineffective, immunomodulating PDT as an adjuvant to surgery is of interest. Towards the development of specialized photosensitizers (PSs) for treating pigmented melanomas, nine new near-infrared (NIR) absorbing PSs based on a Ru(ii ) tris-heteroleptic scaffold [Ru(NNN)(NN)(L)]Cl n, were explored. Compounds 2, 6, and 9 exhibited high potency toward melanoma cells, with visible EC50 values as low as 0.292–0.602 μM and PIs as high as 156–360. Single-micromolar phototoxicity was obtained with NIR-light (733 nm) with PIs up to 71. The common feature of these lead NIR PSs was an accessible low-energy triplet intraligand ( 3 IL) excited state for high singlet oxygen ( 1 O2 ) quantum yields (69–93%), which was only possible when the photosensitizing 3 IL states were lower in energy than the lowest triplet metal-to-ligand charge transfer ( 3 MLCT) excited states that typically govern Ru(ii ) polypyridyl photophysics. PDT treatment with 2 elicited a pro-inflammatory response alongside immunogenic cell death in mouse B16F10 melanoma cells and proved safe for in vivo administration (maximum tolerated dose = 50 mg kg −1 ). Female and male mice vaccinated with B16F10 cells that were PDT-treated with 2 and challenged with live B16F10 cells exhibited 80 and 55% protection from tumor growth, respectively, leading to significantly improved survival and excellent hazard ratios of ≤0.2.